Site visit as time, space and strategy of learnship in a Tourism course - Schulze, Thiago Rodrigues; Teireixa, Renata Plaza (Revista Hipótese, 2016)
Report of the experience of a technical visit realized by Curso Superior de Tecnologia em Gestão de Turismo of IFSP-câmpus Cubatão.